1 - 1 +(-3)+(+5)-(+3)-(-7)
) 2x(-3+4-9)-(-5)
3) (-25):(-5)+16:(-2)
4) - 3 × (-1+5-9)+(-1) ^2 × (-10 )× 0
5) (-2) ^3+ 10 + (-1) ^4 -(-3)^3
Răspunsuri la întrebare
Răspuns de
0
Răspuns:
1-1+(-3)+5-(+3)-(-7)=6
2×(-3+4-9)-(-5)= -11
(-25)÷(-5)+16÷(-2)= -3
-3×(-1+5-9)+(-1)^2+(-10)×0= 15
(-2)^3+10+(-1)^4-(-3)^3= 30
sper sati fie de folos!
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Limba română,
8 ani în urmă
Geografie,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă